Sea Surface Height Changes due to the Tropical Cyclone-Induced Water Mixing in the Yellow Sea, Korea - Kang, KiRyong; Moon, Il-Ju (Frontiers in Earth Science, 2022)
Sea surface height changes due to the tropical cyclone (TC)-induced water mixing in the Yellow Sea, Korea, were investigated using temperature and salinity profile data obtained by two Argo floats during the summer and fall of 2018 and 2020. Strong winds and low pressure, which are important characteristics of TCs, caused horizontal and vertical sea surface water movement and induced water mixing. This caused an increase in mixed layer depth, a decrease in water density, and an increase in specific volume. Specific volume changes related to the water steric effect were directly linked to sea surface height changes. During the TC Soulik (1819) period, the thermocline deepened by more than 10 m, and the steric sea level was increased by more than 3 cm. Other TC cases, such as Jebi (1821), Trami (1824), and Kong-Rey (1825), showed sea level increases of 1–2 cm. In 2020, three TCs – Bavi (2008), Maysak (2009), and Haishen (2010) – showed minor sea level increases (about 0.5–1 cm) because of weak mixing due to their high moving speeds or weak impacts. As a post-TC impact, the water mixing could cause a rise in sea levels due to the steric effect of seawater.